2020
DOI: 10.1038/s41598-020-63187-1
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide identification of Arabidopsis long noncoding RNAs in response to the blue light

Abstract: Long non-coding RNAs (lncRNAs) have been shown in animals to play roles in a wide range of biological processes. In plant, light modulates the growth and development as a key external signal. However, little is known about the role of plant lncRNA in response to light. In this study, we sequenced the messenger RNAs (mRNAs), lncRNAs and microRNAs (miRNAs) in Arabidopsis seedlings under blue light for 2 h and 8 h. Compared to dark, we identified 4197 mRNAs, 375 miRNAs and 481 lncRNAs, or 5207 mRNAs, 286 miRNAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 59 publications
2
29
0
1
Order By: Relevance
“…LncRNAs are a diverse class of RNAs, and the largest class acting as 'biological regulators' that control transcriptional regulation and genome imprinting [9,10]. Numerous noteworthy instances of lncRNAs regulating plant development, disease resistance, nutrient acquisition, and other biological processes through chromatin remodeling, histone modification, pri-mRNA alternative splicing, or acting as 'target mimicry' have been recorded [11][12][13][14][15]. However, few studies have undertaken genome-wide exploration of lncRNAs, their complex regulatory molecular mechanisms, or functional annotation [16].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are a diverse class of RNAs, and the largest class acting as 'biological regulators' that control transcriptional regulation and genome imprinting [9,10]. Numerous noteworthy instances of lncRNAs regulating plant development, disease resistance, nutrient acquisition, and other biological processes through chromatin remodeling, histone modification, pri-mRNA alternative splicing, or acting as 'target mimicry' have been recorded [11][12][13][14][15]. However, few studies have undertaken genome-wide exploration of lncRNAs, their complex regulatory molecular mechanisms, or functional annotation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Specific examples include the brassinosteroid response and the response to blue light in Arabidopsis, and pollen development and the heat stress response in Solanum lycopersicum. Other types of non-coding RNA include sesame, as well as in the cold response in grapevine, the drought response in mulberry, and the drought-responsive multi-tiered regulatory network in drought-tolerant rice [23,30,[51][52][53][54][55][56]. However, a role for miRNAs in regulating the MAPK cascade that operates downstream of the core ABA signaling pathway has not been confirmed in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…These lncRNAs are enriched in certain QTLs (Quantitative Trait Loci) containing genes regulating stress‐receptive pathways (Yuan et al, 2018). lncRNAs have important roles in the modulation of nutrient uptake, growth and development of plants, adaptation of resistance capability against disease and various environmental stresses, regulating some biological activities via modification of histone and chromatin disposition in plants (Corona‐Gomez et al, 2020; Nejat & Mantri 2018; Sun et al, 2020). Chen, Shi, et al (2018) demonstrated that lncRNAs regulate the expression of genes related to various amino acids metabolic pathways (phenylalanine, methionine, and cysteine), photosynthetic metabolism, and phenylpropanoids metabolic pathways to reduce the cadmium toxicity in rice.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%